The internet, teenagers, and sexual health information: a cautionary tale - Sonenstein Freya (BMC, 2012)
Abstract Although most Israeli teenagers have access to the web and many have used the internet to obtain health information, they do not have access to accurate and complete information about contraceptives on Hebrew language websites. Indeed other evidence suggests that teens do not use the web frequently for health information, they are wary of the information obtained from internet sites, and the search engines that they use may not lead them to the most helpful resources. While the internet has the capacity to provide teenagers with information which can assist them in preventing unintended pregnancy and sexually transmitted infections, interventions that address these challenges need to be developed and rigorously tested.